METODE KRITIK SANAD DAN MATAN - Rizkiyatul Imtyas (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2018)
This paper discusses the method of criticism of Sanad and Matan. In the Hadith studies, both aspects are equally important. Sanad is a series of narrators who convey the hadith, while matan is the content / message of the hadith itself. To find out the quality of a hadith we must find out the quality of its transmitters and content. Therefore, this paper is important because it discusses the method of criticism of Sanad and Matan. The source of this paper comes from books/books, and journals that are relevant to the theme of the writing.